A mitochondrial pathway for biosynthesis of lipid mediators - Tyurina, Yulia Y.; Poloyac, Samuel M.; Tyurin, Vladimir A.; Kapralov, Alexander A.; Jiang, Jianfei; Anthonymuthu, Tamil Selvan; Kapralova, Valentina I.; Vikulina, Anna S.; Jung, Mi-Yeon; Epperly, Michael W.; Mohammadyani, Dariush; Klein-Seetharaman, Judith; et al. (Nature chemistry, 2014)
The central role of mitochondria in metabolic pathways and in cell-death mechanisms requires sophisticated signalling systems. Essential in this signalling process is an array of lipid mediators derived from polyunsaturated fatty acids. However, the molecular machinery for the production of oxygenated polyunsaturated fatty acids is localized in the cytosol and their biosynthesis has not been identified in mitochondria. Here we report that a range of diversified polyunsaturated molecular species derived from a mitochondria-specific phospholipid, cardiolipin (CL), is oxidized by the intermembrane-space haemoprotein, cytochrome c. We show that a number of oxygenated CL species undergo phospholipase A 2 -catalysed hydrolysis and thus generate multiple oxygenated fatty acids, including well-known lipid mediators. This represents a new biosynthetic pathway for lipid mediators. We demonstrate that this pathway, which includes the oxidation of polyunsaturated CLs and accumulation of their hydrolysis products (oxygenated linoleic, arachidonic acids and monolysocardiolipins), is activated in vivo after acute tissue injury. © 2014 Macmillan Publishers Limited.
CRIS-Team Scopus Importer:2021-06-08